Evaluating Sufficient Similarity of Botanical Dietary Supplements: Combining Chemical and In Vitro Biological Data. (27th August 2019) - Ryan, Kristen R; Huang, Madelyn C; Ferguson, Stephen S; Waidyanatha, Suramya; Ramaiahgari, Sreenivasa; Rice, Julie R; Dunlap, Paul E; Auerbach, Scott S; Mutlu, Esra; Cristy, Tim; Peirfelice, Jessica; DeVito, Michael J; et al.
Abstract: Botanical dietary supplements are complex mixtures with numerous potential sources of variation along the supply chain from raw plant material to the market. Approaches for determining sufficient similarity (ie, complex mixture read-across) may be required to extrapolate efficacy or safety data from a tested sample to other products containing the botanical ingredient(s) of interest. In this work, screening-level approaches for generating both chemical and biological-response profiles were used to evaluate the similarity of black cohosh ( Actaea racemosa ) and Echinacea purpurea samples to well-characterized National Toxicology Program (NTP) test articles. Data from nontargeted chemical analyses and gene expression of toxicologically important hepatic receptor pathways (aryl hydrocarbon receptor [AhR], constitutive androstane receptor [CAR], pregnane X receptor [PXR], farnesoid X receptor [FXR], and peroxisome proliferator-activated receptor alpha [PPARα]) in primary human hepatocyte cultures were used to determine similarity through hierarchical clustering. Although there were differences in chemical profiles across black cohosh samples, these differences were not reflected in the biological-response profiles. These findings highlight the complexity of biological-response dynamics that may not be reflected in chemical composition profiles. Thus, biological-response data could be used as the primary basis for determining similarity among black cohosh samples. Samples of E. purpurea displayed better correlation in similarity across chemical and biological-response measures. The general approaches described herein can be applied to complex mixtures with unidentified active constituents to determine when data from a tested mixture (eg, NTP test article) can be used for hazard identification of sufficiently similar mixtures, with the knowledge of toxicological targets informing assay selection when possible.